Annotated record of the detailed examination of Mn deposits from DSDP Site 67, Leg 7 (Cores 67-1, 67A-2) - Edward L Winterer; William R Riedel; Ralph Moberly; Johanna M Resig; Loren W Kroenke; E L Gealy; G Ross Heath; P Bronnimann; E Martini; Thomas R Worsley (PANGAEA, 1971)
Site 67 is on the Hawaiian Arch, in the general region selected for one of the Mohole Project sites. Therefore, intensive geophysical surveys have been made in the area. The objectives were to penetrate the entire sedimentary sequence to basement in order to learn the petrology and ages of the sediments and of the seismic reflectors, and to obtain samples of the underlying basement rocks. Well consolidated and bedded volcanic sandstone and mudstone, and claystone were found to extend from the sea floor to a depth of 60 meters, where a layer of hard brown porcelanite stopped the bit. Displaced radiolarians in mud from a core at 60 meters indicate sediments of early Eocene or late Paleocene age are present somewhere above that depth.
Supplement to: Winterer, EL et al. (1971): Site 67. In: Winterer, E.L.; et al., Initial Reports of the Deep Sea Drilling Project, 7, Initial Reports of the Deep Sea Drilling Project, 7, U.S. Government Printing Office, VII, 821-841, https://doi.org/10.2973/dsdp.proc.7.109.1971